Risk of chemotherapy-induced febrile neutropenia by day of pegfilgrastim prophylaxis in US clinical practice from 2010 to 2015. (2nd December 2017) - Weycker, Derek; Bensink, Mark; Lonshteyn, Alexander; Doroff, Robin; Chandler, David
Abstract: Objective: Pegfilgrastim prophylaxis (PP) is recommended 1–3 days following administration of chemotherapy during the cycle. Some patients, however, receive PP before or after the recommended timing. While evidence suggests that risk of febrile neutropenia (FN) may be lower when PP is administered per recommendation, such evidence is based on older data. We undertook a new study to compare FN risk between patients who received PP on the last day of chemotherapy ("day 0") or 4–5 days following chemotherapy ("days 4–5"), versus 1–3 days following chemotherapy ("days 1–3"), using recent data from US clinical practice. Methods: A retrospective cohort design and data from two US private healthcare claims repositories (2010–2016) were employed. Patients received intermediate/high-risk chemotherapy regimens for solid tumors or non-Hodgkin's lymphoma, and PP in ≥1 cycle; all cycles with PP were pooled for analyses. Adjusted odds ratios (OR) for FN during the cycle were estimated for patients who received PP on day 0 or days 4–5, vs. days 1–3, using generalized estimating equations. Results: The study population included 53, 814 patients who received PP in 217, 273 cycles; in 9% of cycles, patients received PP on day 0 (8%) or days 4–5 (<1%). Odds of FN in cycle 1 were significantly higher among patients receiving PP on day 0 (OR: 1.4 [95% CI: 1.2–1.7]) or days 4–5 (1.9 [1.2–3.0]), vs. days 1–3, in that cycle. Results for subsequent cycles of chemotherapy were comparable to those for the first cycle. Conclusions: In this large-scale retrospective evaluation of cancer chemotherapy patients receiving PP in recent US clinical practice, PP was administered before or after the recommended timing in 9% of cycles. FN incidence was significantly higher in these cycles providing additional real-world evidence that PP should be administered the day after chemotherapy in alignment with recently updated US practice guidelines.